Strategi Konter Gerakan Islam Transnasional melalui Dakwah Struktural - Siti Asiyah; Muh. Luthfi Hakim (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2022)
The majority of the Indonesian population who are Muslim with different understandings of Islam is one of the backgrounds for the emergence of new movements that